African History and African under Development: A Revisit of the Rodney Thesis - Udida Undiyaundeye (HUMAN: South Asian Journal of Social Studies, 2021)
African and Africanists scholars formed the intellectual wing of African nationalism; which triumphed in the attainment of political independence of the former colonial possessions in the 1960s. In the course of the nationalist struggle, it was held out that African underdevelopment was coursed by the unequal economic relations between the colonies and the metropolitan countries. Walter Rodney in a brilliant analysis of the low economic situation of the continent held out the prospects of rapid economic advancement of the continent once this colonial hegemony - which came at the heels of the abolition of the over four hundred years of the trans-Atlantic slave trade - was laid to rest. Other scholars pointed out paths to political Stability which, it is generally accepted, is a sine qua non of economic development. Regrettably, almost sixty years on, the African continent is still enmeshed in the backwaters of world economic progress. The Rodney thesis no longer suffices as an explanation of African economic underdevelopment. More so when juxtaposed with some Asian countries which gained political independence contemporaneously with African states. This paper attempts to answer the question of where and why did African political elite get It wrong? By so doing deepen our understanding of the African economic crisis and proffer ways of meeting the challenges so posed.